Hepatoprotector Effect of Coconut Water (Cocos nucifera L.) and Folic Acid to the Liver Histopathological Desccription of Pregnant Wistar Female Rats (Rattus norvegicus) Induced by Carbamate - Muhammad Rosyid Ridho; Aris Prasetyo; Hairrudin Hairrudin (Faculty of Medicine, University of Jember, 2020)
Abstract Carbamate is an insecticide with a working mechanism that inhibits the enzyme acetylcholineestrase (AChE). Obstacles to AChE will cause the formation of excessive free radicals in the body causing oxidative stress and causing lipid peroxidation in body cells, including hepatocyte cells in the liver. Pregnant women have a change in detoxification activity in the liver due to exposure to xenobiotic substances during pregnancy causing a decrease in cytochrome P450 1A2 (CYP1A2) which will cause an increase in free radicals and can damage liver cells. Coconut water contains antioxidants that can neutralize free radicals in the body. While folic acid can encourage improvement in morphology of liver cells. The purpose of this study was to determine the hepatoprotector effect of coconut water and folic acid on the histopathology of the liver of pregnant female wistar rats induced by carbamate. The design of this study is true experimental with a post test only control group design. The sampling method used is simple random sampling. The number of samples in this study were 28 rats divided into 4 groups K (aquades), P1 (carbamate), P2 (carbamate and coconut water), and P3 (carbamate and folic acid). At the end of the study rat liver was taken to then become histological preparations. The One Way ANOVA test results showed a significant difference between groups compared (p <0.05). Post hoc LSD test results showed that group P1 had damaged liver histopathology, there were significant differences with group K and P3 (p <0.05), but there were no significant differences when compared with group P2 (p = 0.826). Meanwhile, the P3 group had significant differences when compared with all groups (p <0.05). The conclusion of this study is that giving coconut water cannot prevent liver damage due to carbamate induction, while folic acid has been shown to prevent liver damage due to carbamate induction, from liver histopathology. Keywords: carbamate, coconut water, folic acid, liver histopathology